Proceedings of the 2014 ACM SIGMOD International Conference on Management of Data 2014
DOI: 10.1145/2588555.2595638
|View full text |Cite
|
Sign up to set email alerts
|

The next generation operational data historian for IoT based on informix

Abstract: In the era of the Internet of Things (IoT), increasing numbers of applications face the challenge of using current data management systems to manage the massive volume of operational data generated by sensors and devices. Databases based on time series data model, like PI Server, are developed to handle such data with operational technology (OT) characteristics (high volume, long lifecycle, and simple format). However, while achieving excellent write performance, these database systems provide limited query ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…It is generally agreed that IoT services require information from historical or real-time data for their own objectives, such as monitoring and optimization [19], [20], [21], [22], [23]. In Refs.…”
Section: Heterogeneity In Iot Message Trafficmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally agreed that IoT services require information from historical or real-time data for their own objectives, such as monitoring and optimization [19], [20], [21], [22], [23]. In Refs.…”
Section: Heterogeneity In Iot Message Trafficmentioning
confidence: 99%
“…In Refs. [19], [20], [22], IoT service systems are required to manage the massive volume of data generated by sensors in various fields, such as smart grids, connected vehicles, and heavy equipment, etc. In Ref.…”
Section: Heterogeneity In Iot Message Trafficmentioning
confidence: 99%
“…To successfully build a real-time analytical solution for a manufacturing organization requires rethinking and reengineering operational processes and data collection, storage, and analysis [116]. Advanced tools, software, and systems are required to capture, store, manage and analyze data sets, all in a timeframe that preserves the intrinsic value of data [117]. Kumaraguru et al [118] identified the need for integrating such data analytical tools into a continuous performance management cycle for SMS.…”
Section: Using Real-time Data Analytics For Continuous Performance Immentioning
confidence: 99%
“…With the need for proactive or forward-looking measurements, some researchers believe that new metrics are needed for productivity since traditional metrics such as utilization rate are not helpful for isolating problem causes and identifying opportunities for improvement [117]. Cesarotti et al [12] proposed overall http://dx.doi.org/10.6028/jres.121.013 equipment effectiveness (OEE) as a quantitative measure of productivity of production equipment in industry.…”
Section: Targeted Performance Objective For Smart Manufacturing -Prodmentioning
confidence: 99%
“…The blast of information will unquestionably turn into a significant issue of IoT [9]. As of not long ago, various studies have endeavored to take care of the issue of inquisitive huge information on IoT [10,11]. Without viable 2 International Journal of Distributed Sensor Networks and proficient investigation, devices will be submerged by this exceptional measure of information.…”
Section: Introductionmentioning
confidence: 99%